(untitled) (Research, Society and Development, 2020)
The aim of the present study was to analyze the mercury content in fish commercialized in Minas Gerais, collected by the Food Monitoring Program of the Health Surveillance of Minas Gerais - PROGVISA, and to verify, based on these values, the risk of fish consumption. The total mercury content in 80 fish samples randomly collected from the Minas Gerais market was analyzed. The analyses were performed by atomic absorption spectrometry with gold amalgamation. From these values, the intake of methylmercury in Minas Gerais was estimated and it was compared with the toxicological reference parameters. Among the samples, 38.8% were from non-predatory fish and 61.2% were from predatory fish. The results indicated that the mercury levels found in most fish samples from Minas Gerais were below the maximum limits allowed by Brazilian legislation. Only 8.2% of the samples of predatory fish showed unsatisfactory results (contents> 1.0 mg / kg), only shark, in this case. In general, non-predatory fish and usually aquaculture fish, such as Tilapia, Panga and Salmon, had low mercury levels. The estimated mercury intake for the population of Minas Gerais was considered acceptable, without appreciable risk to health. Fish consumption following the recommendation of two to three servings per week, excluding fish at the top of the food chain, appears to be safe. The results indicate that mercury contents below the limits established by the Brazilian legislation are important to guarantee intake of this contaminant at safe levels.